Modeling in a three-dimensional world: whitewater park hydraulics and their impact on aquatic habitat in Colorado - Kolden, Eleanor, author; Bledsoe, Brian P., advisor; Wohl, Ellen, committee member; Grigg, Neil S., committee member (Colorado State University. Libraries, 2013)
Whitewater parks (WWPs) are becoming more popular in Colorado rivers and streams, but the effects of WWPs on aquatic habitat and fish passage are poorly understood. This study investigated the use of a three-dimensional (3-D) hydrodynamic model (FLOW-3D®) for assessing effects of WWPs on aquatic habitat. The objective of this study was to compare modeled habitat quality to actual fish biomass and to examine the utility of 3-D modeling (vs. two-dimensional (2-D) modeling) in this hydraulically-complex system. Two sections of a small river in Colorado were modeled: one natural section, and one section containing a WWP with three engineered drop structures. A 2-D habitat suitability analysis for juvenile and adult brown and rainbow trout, longnose dace, and longnose sucker predicted higher habitat quality in the WWPs than the natural reaches for adult brown and rainbow trout at some flow rates, while in-stream surveys showed higher fish biomass per volume in the natural pools. All hydraulic metrics (depth, depth-averaged velocity, turbulent kinetic energy (TKE), 2-D vorticity, and 3-D vorticity) had higher magnitudes in the WWP pools than in the natural pools. In the WWP pools, 2-D model results did not describe the spatial distribution of flow characteristics or the magnitude of variables as well as 3-D results. This thesis supports the use of 3-D modeling for complex flow found in WWPs, but other projects should be evaluated case-by-case to determine if the simplified 2-D rendering of flow characteristics is acceptable. For 3-D modeling to be widely useful, improved understanding of linkages between 3-D aquatic habitat quality and hydraulic descriptors such as TKE, vorticity, and velocity is needed.
Keywords: hydraulic model; whitewater park; vorticity; pool hydraulics; fish habitat; habitat suitability